Uma abordagem simplificada do pensamento Lean em metodologias ágeis - Veiga, Alessandro da (2012)
This project presents a study on the main characteristics that the methodologies of fast development have in common. These are included in Lean premises to predict dynamic questions related to verification and execution of software development project, which don’t have any added value over demand during the completion of tasks, as demonstrated through a case study.